A 6-DoF maneuvering model for the rapid estimation of hydrodynamic actions in deep and shallow waters. (15th December 2020) - Taimuri, Ghalib; Matusiak, Jerzy; Mikkola, Tommi; Kujala, Pentti; Hirdaris, Spyros
Abstract: We present a modular mathematical model and a reference technique for the rapid estimation of maneuvering trajectories and motion time histories of single- and twin-screw propulsion ships. Heave, roll and pitch radiation damping are estimated from a non-linear unified seakeeping/maneuvering time-domain tool using numerical decay tests and then implemented to a 6–DoF model in the form of critical damping and natural period. Short waves are idealised by numerical integration along the vessel's waterline profile and associated hydrodynamic actions are implemented in a response curve format. For the rapid assessment of hull in-plane hydrodynamic forces, derivatives are implemented via semi-empirical methods, CFD or model test data. Results are validated against experiments available for zig-zag and turning cycle trajectories of vessels with different hull forms and propulsion configurations. It is concluded that the approach presented is feasible for the prediction of maneuvering trajectories of existing or new-build vessels and for estimating the evasive velocity in way of contact before grounding. Highlights: We present a 6-DoF modular mathematical model and a reference technique for rapid estimation of maneuvering trajectories of ships. The method applies to both single- and twin-screw propulsion vessels. Short waves are idealised by numerical integration along a vessel's waterline profile. In-plane hydrodynamic forces and derivatives are implemented by available semi-empirical methods, CFD or model test data. Results are validated for turning circle and zig-zag trajectories of a containership, a tanker, a naval ship and a passenger vessel.